PERTUMBUHAN DAN PERKEMBANGAN TUNAS PUAR TENANGAU (Elettariopsis sp.) AKIBAT PERBEDAAN PERIODE SUB KULTUR - Putri Hasanah Jumroh; Luthfi Aziz Mahmud Siregar; Syafruddin Ilyas (Jurnal Agroekoteknologi, 2014)
Puar tenangau is a herbal plant of Zingeberaceae that from Thailand. The Plant has a big potential aspharmacy and traditional medicines, but the spread of this plant was unknown well in Indonesia even soneeded a conservation for this plant. In vitro conservation is a one of alternative. Treatment of periodsubculture is one way to get the explants with optimal growth.The research aimed to determine theappropriate sub culture period to obtain the micropropagation of Puar Tenangau (Elettariopsis sp.) the best asplantlets. The research was carried out in Plant Tissue Culture Laboratory, Department of Agroecotechnology, Faculty ofAgriculture, University of North Sumatera, Medan from November 2012 to August 2013. The research used CompletelyRandomized Design with 1 (one) factor that sub culture period with 4 (four) treatment , which are : 0 week, 2 weeks, 4 weeks,and 6 weeks after culturing from 10 weeks of incubation. The result showed that subculture period not givevaffected on the percentage of explant growt, leaves number, and plant length.Key words : micropopagation, Elettariopsis sp., subculture period